Use of artificial neural network in the analysis of environmental variables associated to litterfall - Sales Rodrigues Aquino, Priscila; Sales Rodrigues, Marcos; Oliveira Castro, Renato Vinícius; Eloi Nappo, Mauro (Comunicata Scientiae, 2016)
The objective of this study was to evaluate, with the use of artificial neural networks, the influence of some environmental variables in litterfall. The study was conducted on the gallery forest along ‘Lava-pés’ stream in Goiás State, Brazil where the experimental site (3 ha) was structured in a grid of 60 litterfall traps, with 0.33 m2 each and held 0.65 m above the soil, georeferenced and spaced at intervals of 32 x 32 m. Litterfall was monthly collected from December 2011 to November 2012. All litterfall samples were manually separated into three fractions: leaves (LE), branch bark (BB), and reproductive parts (RP). Relevance of climate , temporal, spatial and phytosociological variables in litterfall deposition were evaluated, through sensitivity analysis provided by the artificial neural network with the best performance. According to the statistical analysis, all variables were significant in the phenomenon, while the variable time (months of the year) was the most important for litterfall in the evaluated area. Artificial neural networks are shown as a powerful tool for litterfall analysis.